Teletherapy and hospitalizations in patients with serious mental illness during the COVID-19 pandemic: A retrospective multicenter study - Sánchez-Guarnido, Antonio Jose; Machado Urquiza, Beatriz; Soler Sanchez, Maria del Mar; Masferrer, Carmen; Perles, Francisca; Petkari, Eleni (PLOS ONE, 2022)
BackgroundInterventions with patients with Serious Mental Illness (SMI) had to adapt rapidly to the COVID-19 safety restrictive measures, leading to the widespread use of teletherapy as an alternative. ObjectivesThe aims of this study were to compare the use of different intervention modalities with patients with SMI during the first wave of the pandemic and examine their association with emergency hospital visits and hospitalization rates six months later. MethodsRecords of 270 service users of fifteen outpatient mental health services across Spain, were retrospectively assessed. We retrieved clinical data and data on the modality of intervention received (in-person, over the phone, videoconferencing) in three time points (before, during and after the first COVID-19 wave). Also, data were retrieved regarding the frequency of their emergency hospital visits and hospitalization rates, two, four and six months later. ResultsDuring the first wave of the pandemic, teletherapy (over the phone and videoconferencing) was the modality most widely used, whilst in-person therapy sessions were significantly reduced, though they seemed to return to pre-COVID levels after the first wave had passed. Importantly, patients receiving teletherapy during the first wave seemed to have significantly fewer emergency visits and hospitalization rates four and six months later (chi(2) = 13.064; p < .001). Multilevel analyses revealed that patients receiving videoconferencing interventions had fewer hospitalizations six months after the first wave (OR = 0.25; p = .012). ConclusionsUnder challenging circumstances as those created by the COVID pandemic, teletherapy is a useful tool for protection against hospitalizations and can be used as an alternative to in-person therapy, to ensure continuity of care for patients with SMI.
Keywords: telepsychiatry; disorders; JCR; Scopus